Overexpression and Immunosuppressive Functions of Transforming Growth Factor 1, Vascular Endothelial Growth Factor and Interleukin-10 in Epithelial Ovarian Cancer - Liu, Chan-zhen (Springer-Verlag Berlin Heidelberg, 2012)
OBJECTIVE: Transforming growth factor-1 (TGF-β1), vascular endothelial growth factor (VEGF), and interleukin-10 (IL-10) may be critical cytokines in the microenvironment of a tumor, playing roles in immune suppression. This study was conducted to elucidate the roles and immunosuppressive functions of these cytokines in epithelial ovarian cancer (EOC). METHODS: The expression levels of TGF-β1, VEGF and IL-10 in malignant tissue were evaluated by immune- histochemistry and compared with corresponding borderline, benign, and tumor-free tissues. Moreover, relationships among the levels of these cytokines and correlations between expression and the prognosis of EOC were analyzed by Pearson rank correlations and multi-factor Logistic regression. The roles of TGF-β1, VEGF, and IL-10 in the immunosuppressive microenvironment of ovarian cancer were studied through dendritic cell (DC) maturation and CD4+CD25+FoxP3+ Treg generation in vitro experiments. RESULTS: TGF-β1, VEGF, and IL-10 were expressed in 100%, 74.69%, and 54.96% of EOC patients, respectively. TGF-β1 was an independent prognostic factor for EOC. IL-10 was significantly co-expressed with VEGF. In vitro, VEGF and TGF-β1 strongly interfered with DC maturation and consequently led to immature DCs, which secreted high levels of IL-10 that accumulated around the tumor site. TGF-β1 and IL-10 induced Treg generation without antigen presentation in DCs. CONCLUSIONS: TGF-β1, VEGF and IL-10 play important roles in EOC and can lead to frequent immune evasion events.